Poverty traps in natural resource based economy: case of Iran - Hosein Raghfar; Hamid Kurd Bache; Marzie Paktinat (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2012)
Poverty traps as vicious circles preserve people‘s poverty and undermine the poor effort to overcome their own misery. This paper presents an empirical test for a subclass of poverty traps hypotheses. This test is based on the production function to generate multiple equilibrium, while must be present in the region between the equilibrium. Therefore, increasing returns should be strongest when the economy is transiting between steady state than when it is at or near in one of those steady states. We implement this idea by estimating the degree of increasing returns during growth accelerations and growth transitions for a panel of developing and developed economies using World Bank Industrial data. Results of this study show that economies of scale occur where there is collapse in growth. Nevertheless, there are no criteria to distinguish transitory ranges from non-transitory ones. Although, this assumption confirmed economies of scale in industry result in poverty traps.